Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1101/2021.10.21.465335
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphology and gene expression profiling provide complementary information for mapping cell state

Abstract: Deep profiling of cell states can provide a broad picture of biological changes that occur in disease, mutation, or in response to drug or chemical treatments. Morphological and gene expression profiling, for example, can cost-effectively capture thousands of features in thousands of samples across perturbations, but it is unclear to what extent the two modalities capture overlapping versus complementary mechanistic information. Here, using both the L1000 and Cell Painting assays to profile gene expression and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 82 publications
5
36
0
Order By: Relevance
“…High test statistics for L2 distance and a low test statistics for Pearson correlation indicates that the specific MOA “A ∩ B” could not be predicted, either because of incorrect annotations, non-additive or synergistic treatment effects, or a low penetrant phenotype unable to be captured in Cell Painting data. Compared to L1000 gene expression profiles, we observed that gene expression and morphology assays are complementary, but also predict many of the same polypharmacology MOAs ( Fig 5 ) , which is consistent with recent work [ 25 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…High test statistics for L2 distance and a low test statistics for Pearson correlation indicates that the specific MOA “A ∩ B” could not be predicted, either because of incorrect annotations, non-additive or synergistic treatment effects, or a low penetrant phenotype unable to be captured in Cell Painting data. Compared to L1000 gene expression profiles, we observed that gene expression and morphology assays are complementary, but also predict many of the same polypharmacology MOAs ( Fig 5 ) , which is consistent with recent work [ 25 ].…”
Section: Resultssupporting
confidence: 91%
“…Because we had access to the same perturbations with L1000 readouts, we were able to compare cell morphology and gene expression results. We found that both models capture complementary information when predicting polypharmacology, which is a similar observation to a deeper dive which compared the different technology information content [25]. We did not explore multi-modal data integration in this project, as this has been explored in more detail in other recent publications [28,29].…”
Section: Discussionsupporting
confidence: 62%
“…Because the profiles of most variants tend to cluster together within each gene, as observed in the hierarchical clustering of the correlation matrix (Figure 1F), we conclude that the phenotypic variations of alleles remain closely related to the reference gene and rarely result in a major phenotypic disruption that places them in a different cluster. This type of closely related variation is consistent with previous studies in morphological and transcriptional profiling 14,17 , which report that the major factor of variation detected by profiling platforms is first associated with cell lines, then with groups of perturbations that share similar mechanisms, and finally with specific effects of each perturbation.…”
Section: Variant Phenotypes Cluster Consistently With the Corresponding Reference Gene's Phenotypesupporting
confidence: 91%
“…We evaluated this as follows: after acquiring Cell Painting images for each sample (Figure 1B), we transformed them into replicate-level allele profiles using a deep learning-based workflow 12,13 (Figure 1A, see also Methods). We evaluated the quality of profiles using the percent replicating score 14 , measured as the percentage of perturbations whose replicates consistently have higher similarity (reproducible signal) than random sets of perturbations; in this case 83.2% (Figure 1C). 1080x1080), and each channel has been independently rescaled to fit the visible intensity range.…”
Section: Cell Painting Captures a Diversity Of Gene And Allele Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation